2014
DOI: 10.2500/aap.2014.35.3740
|View full text |Cite
|
Sign up to set email alerts
|

Airway acidification in childhood asthma exacerbations

Abstract: Exhaled breath condensate (EBC) is being used increasingly to sample airway lining fluid. In asthmatic patients, the concentration of pH in EBC has been found to be decreased and to be related to airway inflammation. The aim of this study was to determine exhaled pH levels during acute asthma exacerbations in relation to pharmacologic treatment in asthmatic children and compare these with control subjects. Twelve asthmatic children with asthma exacerbation and 27 healthy children were enrolled. Clinical observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…In acute asthma, acidification of EBC has been reported by several independent investigators [9,31,32,33]. These changes in EBC pH have also been observed in pediatric populations [10,34,35,36,37]. In this study, significant reductions in EBC pH values after SIT were observed.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In acute asthma, acidification of EBC has been reported by several independent investigators [9,31,32,33]. These changes in EBC pH have also been observed in pediatric populations [10,34,35,36,37]. In this study, significant reductions in EBC pH values after SIT were observed.…”
Section: Discussionsupporting
confidence: 64%
“…Its ease of collection makes it suitable for studies in the pediatric population [9,10], even in children younger than 4-6 years [11,12,13]. The exhaled air and aerosol contain water vapor that can be condensed by freezing.…”
Section: Introductionmentioning
confidence: 99%
“…Fresh fruit and vegetables are rich dietary sources of antioxidants such as vitamin C, E and β-carotene as well as flavonoids, isoflavonoids and polyphenolic compounds [1,7]. It has been reported that oxidative stress is elevated in asthma and increases further during acute asthma exacerbations [72,73,74], so a high intake of antioxidants may be beneficial. Vitamin C is a major antioxidant in the extracellular respiratory lining fluid that protects immune cells from oxidative stress, and may also contribute to lung growth and development and reduce airway hyper-reactivity, both of which are determinants of childhood and adult lung function [50].…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of a number of biomarkers has been recently investigated and still fosters current research. The poor specificity of many molecules and the complex relationship between symptoms, exacerbations, response to drugs and underlying inflammation hampers the identification of univocal and standardized biomarkers predictive of clinical response [56, 57]. Such biomarkers are still lacking for omalizumab and for current and upcoming biological treatments for severe asthma [55, 58].…”
Section: Discussionmentioning
confidence: 99%